FUNCTIONALITY AND QUALITY OF LIFE IN ELDERLY PEOPLE SUBMITTED TO TOTAL KNEE ARTHROPLASTY - Leonel Preto; Claúdia Pinto; André Novo; Eugénia Mendes; Ilda Barreira; Fidel Lopez-Espuela (Revista Portuguesa de Enfermagem de Reabilitação, 2019)
Objective: To evaluate perception of knee functionality and health-related quality of life (HRQL) in elderly patients submitted to total knee arthroplasty (TKA).